Larger Gray Matter Volume in the Basal Ganglia of Heavy Cannabis Users Detected by Voxel-Based Morphometry and Subcortical Volumetric Analysis - Moreno-Alcázar, Ana; Gonzalvo, Begoña; Canales-Rodríguez, Erick J.; Blanco, Laura; Bachiller, Diana; Romaguera, Anna; Monté-Rubio, Gemma C.; Roncero, Carlos; McKenna, Peter J.; Pomarol-Clotet, Edith (Frontiers in Psychiatry, 2018)
Background: Structural imaging studies of cannabis users have found evidence of both cortical and subcortical volume reductions, especially in cannabinoid receptor-rich regions such as the hippocampus and amygdala. However, the findings have not been consistent. In the present study, we examined a sample of adult heavy cannabis users without other substance abuse to determine whether long-term use is associated with brain structural changes, especially in the subcortical regions. Method: We compared the grey matter volume of 14 long-term, heavy cannabis users with non-using controls. To provide robust findings, we conducted two separate studies using two different MRI techniques. Each study used the same sample of cannabis users and a different control group, respectively. Both control groups were independent of each other. First, whole-brain voxel-based morphometry (VBM) was used to compare the cannabis users against 28 matched controls (HC1 group). Second, a volumetric analysis of subcortical regions was performed to assess differences between the cannabis users and a sample of 100 matched controls (HC2 group) obtained from a local database of healthy volunteers. Results: The VBM study revealed that, compared to the control group HC1, the cannabis users did not show cortical differences nor smaller volume in any subcortical structure but showed a cluster (p<0.001) of larger GM volume in the basal ganglia, involving the caudate, putamen, pallidum and nucleus accumbens, bilaterally. The subcortical volumetric analysis revealed that, compared to the control group HC2, the cannabis users showed significantly larger volumes in the putamen (p=0.001) and pallidum (p=0.0015). Subtle trends, only significant at the uncorrected level, were also found in the caudate (p=0.05) and nucleus accumbens (p=0.047). Conclusions: This study does not support previous findings of hippocampal and/or amygdala structural changes in long-term, heavy cannabis users. It does, however, provide evidence of basal ganglia volume increases.